2020
DOI: 10.3389/fmicb.2020.01328
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Small RNA on the Pseudomonas putida KT2440 Chromosome Is Involved in the Fitness Cost Imposed by IncP-1 Plasmid RP4

Abstract: Plasmids can provide advantageous traits to host bacteria, although they may impose a fitness cost. Chromosome-encoded factors are important for regulating the expression of genes on plasmids, and host chromosomes may differ in terms of their interactions with a given plasmid. Accordingly, differences in fitness cost loading and compensatory co-evolution may occur for various host chromosome/plasmid combinations. However, the mechanisms of compensatory evolution are highly divergent and require further insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The rate at which plasmids are lost from a population probably depends on a combination of these factors and is inversely proportional to 'plasmid persistence'-the ability of a plasmid to maintain itself in the absence of known positive selection for the plasmid. Previous studies from our and other research groups have repeatedly shown that plasmid persistence can improve during growth in the presence or absence of antibiotics (for example [13][14][15][16][17][18][19][20][21][22][23][24] ). However, almost all these studies used planktonic populations.…”
Section: Introductionmentioning
confidence: 85%
“…The rate at which plasmids are lost from a population probably depends on a combination of these factors and is inversely proportional to 'plasmid persistence'-the ability of a plasmid to maintain itself in the absence of known positive selection for the plasmid. Previous studies from our and other research groups have repeatedly shown that plasmid persistence can improve during growth in the presence or absence of antibiotics (for example [13][14][15][16][17][18][19][20][21][22][23][24] ). However, almost all these studies used planktonic populations.…”
Section: Introductionmentioning
confidence: 85%
“…The activation of an SOS response may also induce MGE interactions with potential deleterious effects for the host 18 . Over evolutionary time, compensatory mutations may reduce these genetic conflicts 18,25 . The above illustrates that plasmids interact with host chromosomes; however, very little is known about such interactions at the single-cell level and how these interactions may affect the subpopulation dynamics of their host.…”
Section: Introductionmentioning
confidence: 99%